Penyelesaian Sengketa Melalui Wto Dispute Settlement Mechanism Dalam Menjaga Stabilitas Perekonomian Internasional - Yolanda Febriani; Wahyu Ageng Rizky Dian Pradana; Ridho Saputra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The WTO Dispute Settlement Mechanism (DSM) plays a critical role in maintaining international economic stability through a rule-based trading system. This article examines the effectiveness of the Dispute Settlement Body (DSB) in resolving international trade conflicts, particularly anti-dumping and subsidy cases. Employing a normative legal research methodology, this study analyzes the legal frameworks of the DSU, the Anti-Dumping Agreement, and the SCM Agreement. The Indonesia–EU stainless steel dispute (DS616) and the Airbus-Boeing case serve as primary examples. The findings indicate that while the DSB provides a structured and binding mechanism, it faces significant challenges including the paralysis of the Appellate Body since December 2019, protracted procedures, and regulatory ambiguities in high-tech industries. Despite these challenges, the WTO DSM remains essential for maintaining predictability in the multilateral trading system, though substantial institutional reforms are urgently needed.